HERBS CONSUMPTION AND IMMUNITY DURING THE COVID-19 PANDEMIC - Santosa, Heru; Imelda, Fatwa; Lubis, Namora Lumongga (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
Exposure to COVID-19 causes respiratory tract infections. During the COVID-19 pandemic, there are ways to stay healthy and strengthen the immune system, namely a balanced diet, physical and mental activity, and consuming traditional herbs. This study aimed to describe herb consumption and immunity during the COVID-19 pandemic. The study was an explorative quantitative with a cross-sectional approach. Two hundred people were involved in this study using purposive sampling. Data were collected using traditional herbal consumption questionnaires and an immune status questionnaire (ISQ). Data were analyzed by description. The results show that female was 60%, aged 36–45 years was 33%, Bataknese was 69%, unemployment was 29.5%, senior high school was 50.5%, and greater than or equal to the regional minimum wage was 50.5%. Jamu is a kind of traditional herbal that is the most consumed (75%), respondents consumed less than 250 ml (83%). The results also show that immunity status was good (52%) and poor (48%). It is recommended to take herbs to increase the body's immunity so that it can prevent exposure to COVID-19 in accordance with government recommendations in Indonesia.